Charge migration induced by attosecond pulses in bio-relevant molecules. (24th June 2016) - Calegari, Francesca; Trabattoni, Andrea; Palacios, Alicia; Ayuso, David; Castrovilli, Mattea C; Greenwood, Jason B; Decleva, Piero; Martín, Fernando; Nisoli, Mauro
Abstract: After sudden ionization of a large molecule, the positive charge can migrate throughout the system on a sub-femtosecond time scale, purely guided by electronic coherences. The possibility to actively explore the role of the electron dynamics in the photo-chemistry of bio-relevant molecules is of fundamental interest for understanding, and perhaps ultimately controlling, the processes leading to damage, mutation and, more generally, to the alteration of the biological functions of the macromolecule. Attosecond laser sources can provide the extreme time resolution required to follow this ultrafast charge flow. In this review we will present recent advances in attosecond molecular science: after a brief description of the results obtained for small molecules, recent experimental and theoretical findings on charge migration in bio-relevant molecules will be discussed.